Tetrabutylammonium‐Bromide‐Promoted Synthesis of Spirooxindoles through Alkyne‐Aldehyde C−C Coupling and 1, 3‐Dipolar Cycloaddition Using Ytterbium Triflate Catalyst. Issue 21 (5th June 2020) - Teja, Chitrala; Rahman Nawaz Khan, Fazlur
Abstract: Tetrabutylammonium‐bromide promoted, ytterbium triflate catalyzed one‐pot domino synthesis of spirooxindoles is described. The hydration‐condensation of alkyne, 1 aldehyde, 2 C−C coupling followed by 1, 3‐dipolar cycloaddition of in‐situ generated azomethine ylide from Isatin, 3 and L‐proline, 4 a or sarcosine, 4 b furnished novel spirooxindoles, 5 under solvent‐free green‐chemical conditions, in high regio and stereo selectivities and yields. The regio and stereochemistry of the synthesized derivatives were characterized by 2D NMR Spectroscopic studies. Abstract : A rare earth metal (Ytterbium triflate) catalyzed one‐pot domino synthesis of spirooxindoles from hydration‐condensation of alkyne, aldehyde, C−C coupling followed by 1, 3‐dipolar cycloaddition of azomethine ylide is described. Here, Tetrabutylammonium‐bromide is used as efficient reaction medium; it is a green‐chemical reaction medium to provide spirooxindoles in high regio and stereo selectivities and yields. Stereochemical outcomes of the synthesized molecules were characterized by 2D NMR Spectroscopic studies.